Scotiellopsis levicostata (Chlorophyta) in the Scenedesmaceae (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
The results of morphological and molecular genetic studies of green algae Scotiellopsis levicostata (Scenedesmaceae, Chlorophyceae), found on the territory of Ukraine and put into a collection of cultures of Kyiv National Taras Shevchenko University (strain ACKU 928-10) have been represented . For partial nucleotide sequences of nuclear 18S rDNA gene set the position Scotiellopsis levicostata within clade «Coelastrella» was set. Taxonomic status of the species and its phylogenetic relationships within the clade «Coelastrella» are discussed.
Keywords: green algae, taxonomy, Chlorophyta, Scotiellopsis levicostata.